Postdischarge coping difficulties and influencing factors of pregnant women with gestational diabetes mellitus: A cross‐sectional study - Wen Li (Nursing Open, 2022)
Abstract Aims and objectives To identify coping difficulties after discharge and influencing factors of pregnant women with gestational diabetes mellitus. Design A cross‐sectional descriptive survey was conducted with gestational diabetes mellitus women from four tertiary hospitals in the Shandong Peninsula in China. Methods The study consists of 252 gestational diabetes mellitus women. Survey measures included demographic information, quality of discharge teaching scale, readiness for hospital discharge scale and postdischarge coping difficulty scale. Multiple linear regression analysis was used to explore the factors of coping difficulties after discharge. Results The situation of coping difficulties in pregnant women with gestational diabetes mellitus after discharge is not optimistic. Age, education level, type of birth, parity, quality of discharge teaching and discharge readiness are six factors that significantly influence postdischarge coping difficulties.